Chemical reprogramming of melanocytes to skeletal muscle cells. Issue 2 (1st February 2023) - Yang, Wenjun; Wang, Yaqi; Du, Yuanyuan; Li, Jiyong; Jia, Minzhi; Li, Sheng; Ma, Ruimiao; Li, Cheng; Deng, Hongkui; Hu, Ping
Abstract: Background: Direct cell‐fate conversion by chemical reprogramming is promising for regenerative cell therapies. However, this process requires the reactivation of a set of master transcription factors (TFs) of the target cell type, which has proven challenging using only small molecules. Methods: We developed a novel small‐molecule cocktail permitting robust skin cell to muscle cell conversion. By single cell sequencing analysis, we identified a Pax3 (Paired box 3)‐expressing melanocyte population holding a superior myogenic potential outperforming other seven types of skin cells. We further validated the single cell sequencing analysis results using immunofluorescence staining, in situ hybridization and FACS sorting and confirmed the myogenic potential of melanocytes during chemical reprogramming. We used single cell RNA‐seq that detect the potential converted cell type, uncovering a unique role of Pax3 in facilitating chemical reprogramming from melanocytes to muscle cells. Results: In this study, we demonstrated that the Pax3 ‐expressing melanocytes to be a skin cell type for skeletal muscle cell fate conversion in chemical reprogramming. By developing a small‐molecule cocktail, we showed an efficient melanocyte reprogramming to skeletal muscle cells (40%, P < 0.001). The endogenous expression of specific TFs may circumvent the additional requirement for TF reactivation and form a shortcut for cell fate conversion, suggesting a basic principle that could ease cell fate conversion. Conclusions: Our study demonstrates the first report of melanocyte‐to‐muscle conversion by small molecules, suggesting a novel strategy for muscle regeneration. Furthermore, skin is one of the tissues closely located to skeletal muscle, and therefore, our results provide a promising foundation for therapeutic chemical reprogramming in vivo treating skeletal muscle degenerative diseases.